Commercial impact of agricultural promotion law and world demand in the exports of processed food and agro-based products, case Peru: 2001-2018 - Castagnino Pastor, Claudio (2021)
Faced with a context of global integration and growth of agricultural exports in Peru. The objective of the research was to examine the effected of the Agrarian Promotion Law (law 27360) and world demand during the period 2001- 2018 on the export of the food group of processed food and agro-based products in Peru. The methodology evaluated using the Johansen co-integration test and the Granger causality test: world demand (world Imports) and exports of processed food and agro-based products from the countries of the Andean Community (CAN), where only two members (Peru and Ecuador) had laws to promote the agricultural. Our results showed that there is no causality between the exports of each member of the CAN and world demand in the food group, meanwhile, existed a long-term relationship between exports from Peru and Ecuador with world demand in the food group. The research concluded that Law 27360 and world demand of food group affected positive in the long-term exports of processed food and agro-based products from Peru.